Clinico-etiological profile of children with seizures admitted in a tertiary centre - Ojha, Anil Raj; Ojha, Umesh Raj (Journal of Kathmandu Medical College, 2016)
Background: Seizure is one of the common neurological manifestations and cause of morbidity leading to hospital admission in children. Asserting the causes and types of seizure is vital to management. Objectives: To identify the clinical profile of children and the characteristics of seizures in them. Methods: This is a descriptive study of 32 months duration and involved analysis of the patient records including the demographics of the patients who presented with seizure. Also, type and duration of seizure were noted. All necessary investigations were done to explore the cause of seizure. Sample size was calculated using resift sample size calculator, and the data were entered in Microsoft excel. Statistical analysis was done using statistical package for social sciences version 21. Results: Out of the 5229 children admitted, 533 (10.2%) were admitted for seizure. Male accounted for 346 (65%) cases. 424 (79.5%) of the children were below five years. Fever was associated with seizure in 407 (75.5%) cases. Generalized tonic clinic seizure was observed in 436 (81%) children. 37 children (7%) presented in status epileptics. A total of 370 (68.6%) patients were diagnosed as febrile seizure, 86 (16%) epilepsy, 15 (2.8%) cerebral palsy, 13 (2.4%) neurocysticercosis, 13 (2.4%) tubercular meningitis, 12 (2.2%) viral meningitis, 11 (2%) phylogenic meningitis. The mean (standard deviation) duration of hospital stay was 3.3 (±2.84) days. Conclusion: Seizures are common in less than five years of age and febrile seizure is the most common cause of hospital admission. Most of these seizures are generalized in nature. Journal of Kathmandu Medical College, Vol. 4, No. 2, Issue 12, Apr.-Jun., 2015, page: 55-58